Sosialisasi Penentuan Harga Jual Produk Dalam Rangka Optimalisasi Laba Pada UMKM Di Kelurahan Kebun Sayur - Suci Etri Jayanti; Rika Surianto Zalukhu; Sri Winda Hardiyanti Damanik; Rapat Piter Sony Hutauruk; Daniel Collyn; Murbanto Sinaga; Yenni Mariani Sinurat; Yomeini Margaret Sagala; Ayu Zurlaini Damanik (Jurnal Pelayanan Hubungan Masyarakat, 2023)
The majority of MSME players in Kebun Sayur village, Siantar Timur sub-district, Pematangsiantar city have a poor understanding of how to calculate the correct selling price of products. They also do not understand how to identify costs and classify them appropriately. The selling prices they set for their products are not based on full cost estimates. As a result, the profit they make is not optimal. In view of these problems, a service activity in the form of socialisation was carried out for MSME actors in Kebun Sayur village. This socialisation activity aims to increase the insight and knowledge of MSME actors in Kebun Sayur village, Siantar Timur sub-district, Pematangsiantar city regarding product selling price determination. The socialisation activity was attended by 30 participants. The stages of service activities include preparation stage, implementation stage and evaluation stage. After participating in the service activities, the participants' insight and knowledge in product selling price determination increased. The participants were also able to identify and classify costs in the businesses they manage. This service activity has a positive impact on increasing the insight and knowledge of MSME actors.